Uniaxial tensile and structural properties of poly(vinyl alcohol) films: The influence of heating and film thickness - Aksakal, Baki; Yargi, Onder; Sahinturk, Utkan (WILEY, 2017)
Poly(vinyl alcohol) as pure or composite materials is widely used in the food and textile industries, andbiomedical applications due to some important properties such as uniaxial tensile, biocompatibility, and noncarcinogenicity. Investigation of the influence of the film thickness and heating on the uniaxial tensile, spectroscopic, and surface properties of PVA films investigated in this study is quite important for improving the properties of such materials and their applicability in different conditions. In this study, with the influence of heating, a necking behavior was observed at around 2% for thin films and 4-9% strain for thicker PVA films for which a kind of transition point at around 1-2% strain was observed. The mechanical strength of PVA films, strain at break, and Young's modulus were enhanced greatly as the temperature increased from 80 to around 110 degrees C, and then most of them decreased. The degree of crystallinity increased linearly with the heat temperature from around 36-40%. Although PVA thin films obtained a very smooth surface structure after being heated at 80 degrees C, with increasing heat temperature, the surface roughness of both thin and thick PVA films increased and the PVA thin films obtained more degraded film surface. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44915.
Keywords: FT-IR; ATR spectroscopy; mechanical properties; poly(vinyl alcohol) films; structure-property relationship; thermal effect; POLYVINYL-ALCOHOL; MECHANICAL-PROPERTIES; NANOCOMPOSITES; CRYSTALLINITY; FABRICATION; SEPARATION; NANOTUBE; Polymer Science